Nema-ye Nazdik . Close Up - Kiarostami, Abbas (Reza Zarrin, Ali, 1990)
Duration: 01:33:00 Hossain Sabzian a film lover and huge fan of popular Iranian director Mohsen Makhmalbaf, meets Mrs. Ahankhah, also a fan of one of Makhmalbaf’s films. Posing as Makhmalbaf, Sabzian visits the Ahankhah family several times over the next couple of weeks. He flatters them by saying he wants to use their house for his next film and their sons as his actors. He even obtains a substantial amount of money from them, ostensibly to prepare for the film. Mr. Ahankhah has his suspicions and finds proof that Sabzian is indeed an impostor, who is then arrested by the police. The film, however, does not progress chronologically, and the scenes are re-enactments. The rest of the film is documentary about the trial. By becoming the leading actor in the filmed trial, his obsession with films becomes a reality. The film also gives a unique glimpse of the Iranian legal system.